2000
DOI: 10.1046/j.1365-2044.2000.01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat loss during induction of anaesthesia for elective aortic surgery

Abstract: We have studied core temperature changes occurring during induction of general anaesthesia and surgery in 18 patients undergoing elective aortic aneurysm repair. In the operating theatre, all patients were warmed with a forced-air warmer and a warming mattress, and received warmed (37 degrees C) intravenous fluids. Despite this, mean (SD) [range] core temperatures in the anaesthetic room decreased by 1.5 (0.3)[1.1-2.2] degrees C, while intravascular lines, epidural and urinary catheters were inserted before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…These studies also demonstrate that the core temperatures prevailing after the induction did not change significantly during the first hour of anaesthesia. This is congruent with our findings that the core temperature initially rapidly decreased (14,15). In accordance with the findings of Stoneham et al the temperature decrease in our study correlated with the time interval between the induction of the general anaesthesia and the surgical incision, while the subsequent decrease in temperature during anaesthesia was insignificant (14).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These studies also demonstrate that the core temperatures prevailing after the induction did not change significantly during the first hour of anaesthesia. This is congruent with our findings that the core temperature initially rapidly decreased (14,15). In accordance with the findings of Stoneham et al the temperature decrease in our study correlated with the time interval between the induction of the general anaesthesia and the surgical incision, while the subsequent decrease in temperature during anaesthesia was insignificant (14).…”
Section: Discussionsupporting
confidence: 94%
“…This is congruent with our findings that the core temperature initially rapidly decreased (14,15). In accordance with the findings of Stoneham et al the temperature decrease in our study correlated with the time interval between the induction of the general anaesthesia and the surgical incision, while the subsequent decrease in temperature during anaesthesia was insignificant (14). Therefore, our findings favour the view that an early redistribution of body heat is the major reason for the intraoperative core temperature drop.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Temperatures lower than 36° C (96.8° F) are associated with multiple adverse postoperative outcomes. Even mild hypothermia can cause a negative nitrogen balance (ie, vasoconstriction results in less perfusion to the kidney, which causes less filtering of metabolic waste products from the blood, causing a rise in blood urea nitrogen levels), 3 cause cardiac arrhythmias (eg, bradycardia, premature ventricular contractions, a trial fibrillation, ventricular fibrillation); 3 cause respiratory distress; 3 decrease medication metabolism; 3 delay recovery from anesthesia; 6 impair platelet and clotting cascade function; 2 impair wound healing; 3 increase blood loss and postoperative fluid requirements; 7 increase patient discomfort from shivering and the feeling of being cold; 8 prolong medication action; 2 and reduce resistance to sureical wound infections 2 …”
Section: Behavioral Objectivesmentioning
confidence: 99%
“…Prewarming, however, has not yet become a routine part of preoperative preparation 16 . Stoneham et al 17 found that a period of active preinduction warming is needed to avoid the common decreases in core temperature seen during general anesthesia induction.…”
Section: Level Of Evidence In This Article According To the National mentioning
confidence: 99%